O modelo atômico dos químicos ocultos sob a ótica de Karl Popper, Thomas Kuhn e Paul Feyerabend - Forostecki, Lediany (2012)
The objective of this project is to investigate the epistemological statute of the atomic models presented by Annie Besant and her employees in the end of nineteenth century, the moment of the science history that was characterized by many scientific community attempts for the setting of explanations about the structure of matter. In that moment a group of chemists named "Occultists Chemists" had begun, they proposed an atomic model based on the perception by clairvoyance. The group interacted with physicists that had a key role in the setting of the firsts accepted models in the twentieth century. However, considered too eccentric, faced to its foundation and methodological procedures, the proposal was disregarded by the scientific community of that period. In this project we analyze the atomic model proposal made by Occultists Chemists, in the end of nineteenth century, based on the falsificationism epistemological proposal by Karl Popper, the paradigms and its acceptance by the community, by Thomas Kuhn and the methodological anarchism by Paul Feyerabend. This analysis provides important aids for the discussions around the science nature in the teaching of Chemistry, based on different epistemologies.